Emotional Exhaustion in Late Students Who Are Working in Maintaining Work-Life Balance - Istikhomari, Istikhomari; Kristanto, Andreas Agung; Sofia, Lisda (Psikoborneo: Jurnal Ilmiah Psikologi, 2023)
Students in their development are still trying to find careers that suit themselves, trying to find their own identity, and have a lifestyle according to their desires by working somewhere. Working final students have the responsibility to complete the thesis according to the stipulated time and complete the demands of their work. So, to understand this phenomenon, we will examine the relationship between work-life balance and emotional fatigue in final students who are working. This study aimed to assess the close relationship between work-life balance and emotional burnout. The study was conducted through a quantitative approach with data collection using emotional burnout scale and work-life balance scale. The respondents in this study were 57 final students at Mulawarman University who were working. The study used non-probabiity sampling techniques with purposive sampling methods. Then, the data obtained were analyzed using the Pearson Correlation analysis test. The results of this study showed that there was a negative relationship between work-life balance and emotional fatigue, namely obtained r = -0.291 and p = 0.028 (p < 0.05). This means that the lower the work-life balance, the higher the emotional fatigue experienced. Based on the results of the research obtained, the advice from this study is that the subject can manage a balanced time between personal life and work done by getting enough rest, spending time with family and friends, taking time to please yourself, and not staying up late to complete tasks.Mahasiswa dalam perkembangannya masih berusaha mencari karir yang sesuai dengan dirinya, berusaha menemukan identitas mereka sendiri, dan memiliki gaya hidup sesuai keinginan mereka dengan cara bekerja di suatu tempat. Mahasiswa akhir yang bekerja memiliki tanggung jawab untuk menyelesaikan skripsi sesuai dengan waktu yang ditetapkan dan menyelesaikan tuntutan pekerjaan mereka. Sehingga, untuk memahami fenomena tersebut akan diteliti hubungan antara keseimbangan kehidupan kerja dan kelelahan emosional pada mahasiswa akhir yang sedang bekerja. Penelitian ini bertujuan untuk menilai keeratan hubungan antara keseimbangan kehidupan kerja dan kelelahan emosional. Penelitian dilakukan melalui pendekatan kuantitatif dengan pengumpulan data menggunakan skala kelelahan emosional dan skala keseimbangan kehidupan kerja. Responden dalam penelitian ini sebanyak 57 mahasiswa akhir di Universitas Mulawarman yang sedang bekerja. Penelitian menggunakan teknik non probabiity sampling dengan metode penarikan sampel purposive sampling. Kemudian, data yang diperoleh dianalisis menggunakan uji analisis Pearson Correlation. Hasil penelitian ini menunjukan bahwa ada hubungan negatif antara keseimbangan kehidupan kerja dengan kelelahan emosional yaitu diperoleh nilai r = -0.291 dan p = 0.028 (p < 0.05). Artinya semakin rendah keseimbangan kehidupan kerja maka semakin tinggi kelelahan emosional yang dialami. Berdasarkan hasil penelitian yang diperoleh, maka saran dari penelitian ini adalah subjek mampu mengatur waktu yang seimbang antara kehidupan pribadi dan pekerjaan yang dilakukan dengan cara beristirahat yang cukup, meluangkan waktu bersama keluarga dan teman, meluangkan waktu untuk menyenangkan diri sendiri, dan tidak bergadang untuk menyelesaikan tugas.